A plenitude de um vazio em que a pobreza não é mais paisagem: a periferia em Paulo Lins e Ferréz - Alva Martínez Teixeiro (Estudos de Literatura Brasileira Contemporânea)
This article intends to place Paulo Lins’ novel Cidade de Deus and Ferréz’s novels Capão Pecado and Manual prático do ódio in the panorama of Brazilian contemporary “new-realisms”, evaluating thematic choices and narrative techniques and proce- dures. Also, this study analyses the originality of their prose, noting the cautious distance of their aesthetic philosophies and the fundamental elements of their lit- erary universe –poverty, crime and inequality– from any extreme culture of vio- lence. The analysis of this books seeks to reveal another perspective on the issue of the image of the city and urban poverty, usually sensationalist, and to contribute to a better understanding of the complexity of everyday violence in poor urban communities.